1982
DOI: 10.1007/bf01391377
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid amino acid patterns in hepatic encephalopathy

Abstract: Plasma and cerebrospinal fluid amino acid levels wee measured in 12 cirrhotic patients in grade 0 hepatic encephalopathy and 17 in grade 3-4 hepatic encephalopathy. In 5 of these patients amino acid determinations were performed during the evolution of the encephalopathy. No correlation was found between the degree of hepatic encephalopathy and the plasma amino acid imbalance. In the CSF of cirrhotic patients without encephalopathy, a significant increase was found in nearly all amino acids, including those kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 19 publications
4
17
1
Order By: Relevance
“…The changes in the plasma and cerebrospinal fluid amino acid pattern after portacaval anastomosis reported here are in accordance with previous reports on plasma aminograms in dogs with PCS [1,13,25] and amino acid changes in CSF following PCS in animals [11,29] and in patients with cirrhosis of the liver [4]. After ammonium acetate infusion into the dogs with PCS the plasma levels of phenylalanine and tyrosine increased, as has been reported in patients with liver cirrhosis after an oral load of ammonium chloride [14].…”
Section: Changes In Plasma and Csf Amino Acid Patternssupporting
confidence: 93%
See 1 more Smart Citation
“…The changes in the plasma and cerebrospinal fluid amino acid pattern after portacaval anastomosis reported here are in accordance with previous reports on plasma aminograms in dogs with PCS [1,13,25] and amino acid changes in CSF following PCS in animals [11,29] and in patients with cirrhosis of the liver [4]. After ammonium acetate infusion into the dogs with PCS the plasma levels of phenylalanine and tyrosine increased, as has been reported in patients with liver cirrhosis after an oral load of ammonium chloride [14].…”
Section: Changes In Plasma and Csf Amino Acid Patternssupporting
confidence: 93%
“…Tryptophan is the precursor of serotonin, an inhibitory neurotransmitter, and is found in high concentrations in CSF during hepatic coma both in patients with liver cirrhosis and in animals with PCS [22,28,29]. It has been assumed that the plasma level of free tryptophan shows a good correlation with the neurologic status of patients with cirrhosis of the liver [4,19].…”
Section: Changes In Plasma and Csf Amino Acid Patternsmentioning
confidence: 99%
“…The elevation of these aromatic amino acids leads to increased synthesis of 5HT, DA, and NA in the brain (Cascino et al, 1982;Bernardini and Fischer, 1982;Fanelli et al, 1986). This process may play a role in the pathogenesis of HE (Lozeva-Thomas, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein and amino acid metabolism are hallmarks of cirrhotic-stage liver disease, caused by a loss of the ability of the liver to regulate the metabolism of both circulating and tissue proteins and amino acids. [28][29][30] Diminished BCAA concentrations have been reported in association with malnutrition in hemodialysis patients. 31 However, we found that in patients with end-stage liver disease, circulating amino acid values are poorly indicative of nutritional status.…”
Section: Discussionmentioning
confidence: 99%